Analyzing the guiding principles of AI ethics: A framing theory perspective on the communication of ethical considerations in artificial intelligence (AI) - Younas, Asifa (BOHR International Journal of Internet of things, Artificial Intelligence and Machine Learning, 2024)
Various organizations have created AI ethics standards and protocols in an era of rapidly expanding AI, all to ensure ethical AI use for the benefit of society. However, the ethical issues raised by AI’s societal applications in the actual world have generated scholarly debates. Through the prism of framing theory in media and communication, this study examines AI ethics principles from three significant organizations: Microsoft, NIST, and the AI HLEG of the European Commission. Institutional AI ethics communication must be closely examined in this rapidly changing technical environment because of how institutions frame their AI principles.